THE CONSTRUCTION OF THE IMAGE OF THE “IDEAL WIFE” IN INTERCULTURAL MARRIAGES: A CASE STUDY ON THE YOUTUBE VIDEO “YOUNGER SINGAPORE MEN LOOKING FOR VIETNAM BRIDES - Jie, Li (International Review of Humanities Studies, 2025)
This study explores the process of constructing the image of the “ideal wife” in intercultural marriages, using the video Younger Singapore Men Looking for Vietnam Brides as a case study. It analyzes the economic and cultural motivations of Singaporean men in choosing Vietnamese wives. By applying Judith Butler’s theory of gender performativity and Henri Tajfel’s social identity theory, the study examines how Vietnamese brides are symbolized as the “ideal partner” and how this phenomenon reflects modern gender role conflicts and identity reconstruction. Through an analysis of interviews in the video and relevant comments, the research reveals the dynamic interaction between gender expectations, economic considerations, and cultural identity. This study also offers a new perspective on understanding gender culture and social structures in cross-border marriages in Southeast Asia.